Comparative study of quarkonium transport in hot QCD matter - Andronic, Anton; Gossiaux, P. B.; Petreczky, Peter; Rapp, R.; Strickland, Michael T.; Blaizot, Jean-Paul; Brambilla, Nora; Braun-Munzinger, Peter; Chen, B.; Delorme, Stefan; Du, X.; Escobedo, M. A.; et al. (The European physical journal. A, Hadrons and nuclei, 2024)
This document summarizes the efforts of the EMMI Rapid Reaction Task Force on “Suppression and (re)generation of quarkonium in heavy-ion collisions at the LHC”, centered around their 2019 and 2022 meetings. It provides a review of existing experimental results and theoretical approaches, including lattice QCD calculations and semiclassical and quantum approaches for the dynamical evolution of quarkonia in the quark-gluon plasma as probed in high-energy heavy-ion collisions. The key ingredients of the transport models are itemized to facilitate comparisons of calculated quantities such as reaction rates, binding energies, and nuclear modification factors. A diagnostic assessment of the various results is attempted and coupled with an outlook for the future.